Retrospective analysis of the clinical behavior of oral hairy leukoplakia in 215 HIV-seropositive patients - Daniela Assis do VALE; Fabiana Martins e MARTINS; Paulo Henrique Braz da SILVA; Karem López ORTEGA
Abstract Oral manifestations are common findings in human immunodeficiency virus (HIV) infected patients and frequently influence the overall health. Oral hairy leukoplakia (OHL) is strongly associated with HIV infection demonstrating its relationship with the individual's immune status and progression of immunosuppression. This study aims to retrospectively evaluate OHL in HIV patients, analyzing its incidence, demographic aspects and possible changes in clinical and epidemiological profile of the disease over 17 years. The records of 1600 HIV-infected patients were reviewed. The data were correlated and analyzed, considering HIV exposure category, age, gender, harmful habits, CD4 level, use and type of antiretroviral. OHL was observed in 215 (13.4%) patients. Most were men in the fourth decade of life, 171 (79.5%) and 112 (52,1%) respectively, but an increase in the incidence of OHL among female patients and those in the fifth decade of life was observed. Tobacco smoking was the most frequent harmful habit reported by 114 (68%) patients. OHL occurred mostly in patients with CD4 counts between 200 and 500 cells/mm3 35 (55.5%). The lower incidence of OHL was found among patients using at least one non-nucleoside reverse transcriptase inhibitor (NNRTI). OHL is related to CD4 count, use of ARVT and tobacco smoking and is also more prevalent in men in the fourth decade of life. These characteristics were recognized in absolute values, but when verifying the behavior over the years we noticed that the incidence of OHL is decreasing and its epidemiological characteristics changing.